Emergence of collective effects in complex plasmas - Joshi, Eshita; Justus Liebig University Giessen (My University, 2024)
This work is dedicated to studying the emergence of collective effects in ionised gases with micrometre sized particles immersed in them, also known as complex plasmas. These are often used as model systems to study a variety of emergent phenomena since the particles are large enough to be imaged directly. I present a theoretical model of the self-formation of droplets based on recent experiments performed in weightless complex plasmas. The model is based on balancing the ion drag force with electrostatic repulsion to explain the formation of stable droplets. It produces quantitative results that predict the size of a droplet as a function of the plasma parameters in agreement with the experimental observations. For the ﬁrst time, this model causally connects the size of the droplet to plasma parameters (such as the electron temperature). Not only can the model predict what size and shape of droplets may form in the experiment given the parameters, but it can also determine the parameters from the size of the observed droplet. This allows the observation of droplets to be used as a diagnostic tool to determine plasma parameters in complex plasma experiments. Beyond this, I investigate additional collective ﬂuid effects such as the formation of shocks and the onset of turbulence by simulating a ﬂow of microparticles past a spherical obstacle in a complex plasma. This work is one of the ﬁrst systematic particle-resolved investigations of turbulence, in which I demonstrate that the formation of shocks is important for the onset of turbulence in damped systems. By simulating a supersonic ﬂow, I can reliably generate Mach cones and bow shocks both up- and downstream of the obstacle. I report the observation of double bow shocks in these simulations for the ﬁrst time in complex plasmas, showing a similar structure as observed in astrophysical plasmas. In regions where particles ﬂow directly into a shock, the increased microparticle density - and hence, strength of interactions - triggers the onset of turbulence. This link between increased microparticle density and the onset of turbulence in damped ﬂuids is in agreement with previous complex plasma experiments. I report that the onset of turbulence in the simulations depends on parameters such as particle charge and ﬂow speed. A non-turbulent simulation can be made turbulent by changing one of these two parameters. Both of these parameters can be controlled in experiments, allowing the simulations to predict and control the onset of turbulence in complex plasma experiments even under the inﬂuence of damping, opening the pathway towards detailed studies of the onset and control of turbulence at the level of individual particles. Finally, I study the onset of electrorheological effects through the formation of string-like clusters (SLCs) based on microgravity experiments. This process is led by the deformation of the ion shielding cloud around the particles due to an alternating ion ﬂow. I mimic this in the simulations by placing a positive wake charge in-front of and behind the particle to modify the interparticle potential. By doing so, I can reproduce the formation, destruction, and recrystallisation of SLCs as seen in the experiments with qualitatively similar results. I test whether an effective long-range interparticle attraction is required to produce SLCs, and report that this is not the case. The excellent qualitative agreement between experiment and simulation is deﬁnitive proof that effective long-range interparticle attraction is not a necessity for electrorheological effects in complex plasmas. Overall, this thesis advances the knowledge of emergent phenomena in complex plasmas in a variety of conditions. As complex plasma experiments can resolve individual particle dynamics, this work can be used to inform future investigations of collective effects at the particle-resolved level.
Entstehung von kollektiven Effekten in komplexen Plasmen
Keywords: turbulence; numerical simulations; plasma; complex plasma; microgravity; ddc:530